2019
DOI: 10.1186/s12934-019-1097-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic metabolic pathway for the production of 1-alkenes from lignin-derived molecules

Abstract: BackgroundIntegration of synthetic metabolic pathways to catabolically diverse chassis provides new opportunities for sustainable production. One attractive scenario is the use of abundant waste material to produce a readily collectable product, which can reduce the production costs. Towards that end, we established a cellular platform for the production of semivolatile medium-chain α-olefins from lignin-derived molecules: we constructed 1-undecene synthesis pathway in Acinetobacter baylyi ADP1 using ferulate,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 49 publications
1
48
2
Order By: Relevance
“…To obtain higher tolerance toward inhibitory substrates, strain optimization could be applied through adaptation and laboratory evolution (Dragosits & Mattanovich, ) or by genetic engineering. In a recent study by Luo, Lehtinen, Efimova, Santala, and Santala (), the tolerance of A. baylyi ADP1 toward ferulate was increased up to 180 mM by adaptive laboratory evolution. For example, Benndorf, Loffhagen, and Babel () showed that by inducing Acinetobacter calcoaceticus 69‐V ( A. baylyi previously referred to as A. calcoaceticus ) with 14 mM of phenols or catechols heat shock proteins were produced to increase tolerance toward oxidative stress.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To obtain higher tolerance toward inhibitory substrates, strain optimization could be applied through adaptation and laboratory evolution (Dragosits & Mattanovich, ) or by genetic engineering. In a recent study by Luo, Lehtinen, Efimova, Santala, and Santala (), the tolerance of A. baylyi ADP1 toward ferulate was increased up to 180 mM by adaptive laboratory evolution. For example, Benndorf, Loffhagen, and Babel () showed that by inducing Acinetobacter calcoaceticus 69‐V ( A. baylyi previously referred to as A. calcoaceticus ) with 14 mM of phenols or catechols heat shock proteins were produced to increase tolerance toward oxidative stress.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, using substrates such as LRAs pose a challenge for wax ester production and preservation due to their inhibitory effects at elevated concentrations. Unspecific strategies, such as adaptive laboratory evolution could allow the use of higher substrate concentrations (Luo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14] It is tolerant towards lignocellulose related monomeric compounds, such as phenolic acids, acetate, and ethanol, which typically inhibit microbial growth. [15][16][17][18] Furthermore, it can utilize monomeric lignin compounds through catabolic β-ketoadipate pathway, which efficiently funnels carbon to biomass and storage compound synthesis. 17,19,20 The Acinetobacter genera and A. baylyi ADP1 have also been identified with lignin depolymerizing activities.…”
Section: Introductionmentioning
confidence: 99%
“…In microbial oxygen removal, medium‐ to long‐chain hydrocarbons are the target molecules; these are semivolatile compounds, which turns collection from a culture vessel without cell harvesting or production extraction into a reality . In such a microbial process, the resulting molecules may accumulate extracellularly and may be collected from the culture vessel without harvesting of cells.…”
Section: Chemical Versus Microbial Deoxygenationmentioning
confidence: 99%
“…Natural fatty acid metabolism in microorganisms through a synthetic route offers the formation of 1‐undecene from glucose. In such a process, a decarboxylase enzyme acts as an oxygen activator, which results in the corresponding terminal alkene . Deoxygenation occurs through the route of one‐step fatty acid decarboxylation of FFAs, which is catalyzed by UndA for the production of 1‐undecene.…”
Section: Chemical Versus Microbial Deoxygenationmentioning
confidence: 99%